GaAs/AlAs/AlGaAs quantum well infrared photodetector - Fan, Weijun (2008)
The objective of this project is to calculate and analyze the subband energy levels in quantum wells of GaAs/AlGaAs and GaAs/AlAs/AlGaAs with eight-band K·P modes, and to design Quantum Well Infrared Photodectors (QWIP) from the two kinds of QWs, and to evaluate the performance of two kinds of QWIPs in comparison with the simulation results. In this project, the n-type QW structures of GaAs/AlGaAs and GaAs/AlAs/AlGaAs with specific parameters are grown by all solid source MBE on the GaAs substrates. Two material systems and quantum well structures are systematically characterized and investigated. After characterization, two kinds of samples are fabricated into QWIP devices. Some of them show evident photoresponse which well matches simulation results.